Загальна декларація мовних прав і права мовних меншин - Пономаренко, В.П. (Мовознавство, 2013)
У статті розглядаються основні положення Барселонської декларації мовних прав 1996 р. і мовна ситуація в Каталонії та інших регіонах Іспанії (Країна Басків, Галісія), а також Італії і Швейцарії стосовно статусу, поширення й розвитку регіональних мов. The article deals with the main clauses of Barcelona Universal Declaration of Linguistic Rights of 1996, linguistic situation in Catalonia and other regions of Spain (Basque Country, Galicia), as well as of Italy (Sardinia, Friuli), Switzerland (Graubiinden, where also Romansh, a Rhaeto-Romance language, is spoken) as for status, diffusion and development of regional languages.
The afore-said Declaration is one of the most important international documents concerning linguistic issues.lt regards mainly endangered languages. Barcelona is the capital city of Catalonia, an autonomous community of Spain where the Catalan language, often oppressed in the past, is actually not only officially recognized but widely spread and promoted also by the authorities at all levels. Despite certain exaggerations, the situation in Catalonia can be an example of persistent upholding of linguistic rights, national culture and traditions. Although national self-consciousness is also evidently present in other linguistic minorities both in Spain and in other European countries, the percentage of ethnic Basques, Galicians, Sardinians, Friulians or Ladin people speaking and using actively their languages and protecting their rights is considerably smaller. So far, the solution of problems related to languages, which are still topical in most multinational countries of today’s Europe, depends not only on legislation conditions, favorable in most cases, and official status, national or regional, but also on civil position and mentality of speakers belonging to ethnic and linguistic minorities.